Food process modelling - Tijskens, L. M. M.; Hertog, M. L. A. T. M.; Nicolaï, B. M. (Online access with JISC subscription agreement: Knovel., 2001)
Food process modelling provides an authoritative review of one of the most exciting and influential developments in the food industry. The modelling of food processes allows analysts not only to understand such processes more clearly but also to control them more closely and make predictions about them. Modelling thus aids the search for greater and more consistent food quality. Written by a distinguished international team of experts, Food process modelling covers both the range of modelling techniques and their practical applications across the food chain.